1992
DOI: 10.1021/bi00122a010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphate transport across the human erythrocyte membrane by chemical modification of sulfhydryl groups

Abstract: Effects of sulfhydryl-reactive reagents on phosphate transport across human erythrocyte membranes were examined using 31P NMR. Phosphate transport was significantly inhibited in erythrocytes treated with sulfhydryl modifiers such as N-ethylmaleimide, diamide, and Cu2+/o-phenanthroline. Quantitation of sulfhydryl groups in band 3 showed that the inhibition is closely associated with the decrease of sulfhydryl groups. Data from erythrocytes treated with diamide or Cu2+/o-phenanthroline demonstrated that intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The site of conformational change of the dimeric cytoplasmic domain due to hemoglobin binding is believed to be the cluster of sulfhydryl groups that lie ~100 A from the N-terminus as shown by measuring sulfhydryl reactivity on hemoglobin binding (Salhany & Cassoly, 1989). Further, it has been reported that chemical modification of the sulfhydryl groups in the cytoplasmic domain of band 3 inhibits phosphate transport across the human eryhtrocyte membrane (Yamaguchi & Kimoto, 1992). This model for conformational changes in the cytoplasmic domain transmitted to the TMD causing changes in the transport activity of the TMD gives support to the view that band 4.2 could act as a modulator of anion transport by band 3 by acting through the cytoplasmic domain.…”
Section: Transport Studiesmentioning
confidence: 69%
“…The site of conformational change of the dimeric cytoplasmic domain due to hemoglobin binding is believed to be the cluster of sulfhydryl groups that lie ~100 A from the N-terminus as shown by measuring sulfhydryl reactivity on hemoglobin binding (Salhany & Cassoly, 1989). Further, it has been reported that chemical modification of the sulfhydryl groups in the cytoplasmic domain of band 3 inhibits phosphate transport across the human eryhtrocyte membrane (Yamaguchi & Kimoto, 1992). This model for conformational changes in the cytoplasmic domain transmitted to the TMD causing changes in the transport activity of the TMD gives support to the view that band 4.2 could act as a modulator of anion transport by band 3 by acting through the cytoplasmic domain.…”
Section: Transport Studiesmentioning
confidence: 69%
“…Casey and coworkers (255, 366-368) have used cysteineless band 3 for informative studies of topology and function by cysteine scanning mutagenesis, as reviewed by Reithmeier et al (20). Despite the fact that band 3 has no cysteine residues that are necessary for transport, treatment with N-ethylmaleimide (NEM) or oxidative stress inhibits red cell anion transport to varying degrees (369)(370)(371)(372)(373)(374)(375).…”
Section: Effects Of Oxidative Stress Thiol Status and Tyrosine Phosphorylationmentioning
confidence: 99%
“…The importance of thiol groups for the function of numerous proteins involved in transport processes has been well demonstrated. Thiol dependent transporters include the vacuolar ATPase [5], the Ca# + pump ATPase [6], simple channels for water and urea [7,8], gated chloride dependent K + channel flux [9], and a variety of mobile carriers for glucose [10,11], nucleosides [12], choline [13], phosphate [14][15][16], amino acids [17], fatty acids [18], anions [18,19] and cations [20]. However, in earlier studies using lysosomal membrane vesicles the sulphate transporter did not appear to be particularly dependent upon sulphydryl (thiol) groups as NEM had no effect on trans-stimulation of sulphate transport [1].…”
Section: Introductionmentioning
confidence: 99%